A study of the metal matrix friction materials of hot pressing using Taguchi method. Issue 1 (2nd January 2018) - Luo, Shenq-Yih; Weng, Chih-Yuan
Abstract: The effect of the different compositions of the copper matrix friction materials fabricated by hot press on the coefficient of friction and wear rate using Taguchi method was investigated. Besides, their wear mechanisms were studied as well. The metal matrix of the formula was Cu, Fe, Sn and Zn, the lubricant was graphite, and the friction modifier was SiO2 . The experiment results showed that under the larger-the better for the coefficient of friction and the smaller-the better for the wear rate using Tachugi method, the best compositions for getting a best friction performance were 42wt%Cu-0wt%Fe-6wt%Sn-2wt%Zn-20wt%C-30wt%SiO2 with the coefficient of friction of 0.5–0.65 and wear rate below 1 × 10 −7 cm 3 /kgf-m. The more proportion of copper amount in the copper matrix friction material showed the larger coefficient of friction and the smaller wear rate. Furthermore, the more amount of tin and silicon oxide displayed the better coefficient of friction and wear rate. The wear mechanisms for the copper matrix friction materials mainly showed abrasive wear, adhesive wear and mechanical fatigue.